Battery management system - Ng, Sze Zhuang (2017)
DC microgrid had gained its popularity into the modern world with the increased in DC loads globally. The advancement of the semiconductor technology had made power conversions in Direct Current (DC) much reliable and efficient. Energy Storages (ESs) were used in the DC microgrid to mitigate the variations between the loads and the generations. However, different type of ESs, such as batteries and ultracapacitors, exhibit different characteristics and had different properties. Thus, a Hybrid Energy Storage System (HESS) implementation would be beneficial for the operation to attain optimal response with the complementary properties of different ESs. With multiple ESs connected, an Energy Management System (EMS) would be required to manage the power distribution and State of Charge (SoC) restoration of the ESs.